Problemy professionalnogo sporta: provovoj aspekt - Kogan, O. S. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
An official recognition in 1999 "The federal law on physical culture and sports" the status of the professional sports rightfully can be considered as the basis for the formation of the new branch - the sports' industry. The sports of the maximum achievements exist in Russia from the moment of the foundation of sports movement. The occurrence of the term "professional sports" assumes an opportunity to consider the sports activity as any other industrial field of the activity. With the recognition of the status of the professional sports there is actual the recognition of the complex of the adverse factors of the professional sports activity, to which the athlete adjoins to provide during the work all probable kinds of the preventive maintenance, the social protection and the social help at infringement of his state of the health and the loss of the professional work capacity as it is accepted in any other branch described by any harmful working conditions. The positions presented in the article can be used for creation of the uniform unified system of the obligatory certification of means of the physical improvement and sports services for various layers of the population.